Hormetic UV-C irradiation retards postharvest senescence of Pleurotus ostreatus via ROS metabolism and antioxidant gene upregulation - Hafiz Muhammad Mubeen; Numan Khan; Rouna Li; Jiayi Hu; Yingying Zhang; Muhammad Shahar Yar; Muhammad Bilal; Mei Li (Postharvest Biology and Technology, 2026)

Molecular insights and antibiotic resistance genes characterization in clinical Vibrio cholera isolates from patients in Peshawar, Pakistan - Muhammad Atif; Jawad Ahmad; Aisha Irfan; Hafiza Misbah Ahmad; Aiman Waheed; Khalid Khan; Numan Fazal (Molecular Biology Reports, 2026)

Seroprevalence and risk factors of Mycobacterium avium subsp. paratuberculosis in dromedary camels of Southern Punjab, Pakistan - Aliza Ali; Mughees Aizaz Alvi; Muhammad Hammad Hussain; Muhammad Numan; Junaid Ahmad; Muzafar Ghafoor; Muhammad Khalid Mansoor; Muhammad Saqib (Tropical Animal Health and Production, 2026)

Variation in available phosphorus in acidic farmland soil in response to inorganic amendments: A meta-analysis - Yaxin Liu; Kailou Liu; Jing Huang; Muhammad Numan Khan; Hongen Liu; Jie Chen; Huimin Zhang; Tianfu Han (Soil and Tillage Research, 2026)

An overview of smart windows in Passivhaus design for enhanced energy efficiency and comfort in net-zero buildings - Alejandro Moreno-Rangel; Muhammad Norhaffis Mustafa; Muhammad Sheraz Ahmad; Arshid Numan; Mohammad Khalid (Innovative Infrastructure Solutions, 2026)

Electrodialysis for sustainable water desalination: Principles, applications, challenges, and future directions - Subhan Mahmood; Numan Mahmood; Muhammad Usman Liaquat; Faizan Ikhlaq; Hamza Shehzad; Shun Yao (Journal of Environmental Chemical Engineering, 2026)

Biomimetic surface architectures inspired by cacti: Progress in fog water harvesting systems - Muhammad Numan Nawaz; Sadaf Bashir Khan; Weifang Yuan (Journal of Environmental Chemical Engineering, 2026)

Omics-driven soil bioremediation of emerging contaminants: Integrating sensors, digital twins, and microbial biotechnology - Asad Shah; Mohammad Nauman Khan; Waqar Ali; Muhammad Numan Khan; Hidayat Ullah; Zahra Barati; Adil Farooq Lodhi; Lixiao Nie (Applied Soil Ecology, 2026)

Machine learning-guided discovery of mitogen-activated protein kinase 7 (MAPK7 inhibitors): integrating virtual screening, docking, and molecular dynamics simulations - Chandni Hayat; Amar Ajmal; Nayab Gul; Muhammad Numan; Haleema Bibi; Naveed Akhtar; Laiba Sultan; Arif Ali; Muhammad Tahir Khan; Muhammad Saqib (In Silico Pharmacology, 2026)

Genetic and morphological data indicate the occurrence of a Rhipicephalus sp. and the absence of Rhipicephalus linnaei in Pakistan - Muhammad Numan; Zaibullah Khan; Sher Bahadar Khan; Mohibullah Shah; Iram Liaqat; Itabajara da Silva Vaz Junior; Lidia Chitimia-Dobler; Abid Ali; Zhihua Sun; Mashal M. Almutairi (Tropical Animal Health and Production, 2026)

Bacteriophage-based vaccination platform for antigen discovery and development of next-generation vaccines - Shahzar Khan; Nadia Ilyas; Aneela Nawaz; Muhammad Ismail Khan; Momina Aamir; Nauman Ahmed Khalid; Aamer Ali Shah; Numan Saleh Zada; Ghulam Shabbir; Malik Badshah; Samiullah Khan (Next Research, 2025)

Arbuscular mycorrhizal fungi and soil microbial communities under nitrogen deposition in nutrient-limited grasslands: a systematic review - Muhammad Numan Ali; Md Akramul Islam; Saddam Saqib; Muhammad Sufhan Tahir; Tahir Saadu; Ans Saeed; Aqarab Husnain Gondal (Symbiosis, 2025)

MnFe2O4 thin film electrodes via AACVD: A facile route for enhanced oxygen evolution reaction - Alishbah Zaka; Misha Aftab; Nudrat Fatima; Khola Mashood; Muhammad Adeel Asghar; Arshid Numan; Muhammad Sheraz Ahmad; Ali Haider; Mudassir Iqbal; Waqas Ali Shah; Muhammad Adil Mansoor (Fuel, 2025)

Mechanisms of lime-induced N2O mitigation in acidic soils: A meta-analysis of microbial activity and substrate dynamics - Kiya Adare Tadesse; Tianfu Han; Zhe Shen; Nano Alemu Daba; Jiwen Li; Muhammad Numan Khan; Asad Shah; Huimin Zhang (Applied Soil Ecology, 2025)

Development of a hydrodynamic model of the irrigation canal network by using HEC-RAS: a case study of Layyah Canal Division, Pakistan - Numan Ijaz; Sajjad Haider; Muhammad Muaaz (Modeling Earth Systems and Environment, 2025)

Development and structural performance evaluation of consistent-sized interlocking clay bricks as an alternative to conventional bricks: an experimental investigation - Muhammad Numan; Muhammad Rizwan Riaz; Rizwan Azam; Muhammad Faraz Javaid; Mohamed Zawam (Innovative Infrastructure Solutions, 2025)

Prevalence of Staphylococcus aureus and Antimicrobial Drug Residues in Chicken Liver its Antibiogram Analysis and Implications on Public Health - Gulzar Ahmad; Malik Muhammad Rizwan; Faryal Azam; Muhammad Ijaz; Ainee Urooj Khan; Shamsher Khan; Muhammad Khan; Hafsa Shah; Noor Muhammad; Zia Ur Rahman; Numan Fazal; Sajjad Ullah; et al. (Indian Journal of Microbiology, 2025)

Potential role of inoculum size in biomass accumulation and antioxidant secondary metabolites production in adventitious root cultures of Stevia rebaudiana - Naveed Ahmad; Nisar Ahmad; Muhammad Sajid; Kamran Rauf; Mudassar Iqbal; Muhammad Numan; Irfan Ullah; Amir Khan; Wahidah H. Al-Qahtani; Mostafa A. Abdel-Maksoud; Hamada AbdElgawad; Babar Iqbal; et al. (Plant Biosystems, 2025)

Development of growth curve and estimation of genetic parameters of Nili-Ravi buffalo calves from birth to one year of age through non-linear models - Asad Abbas; Atia Basheer; Moinina Nelphson Kallon; Numan Sharif; Heydar Ghiasi; Tariq Mehmood; Burhane Azam; Anjum Khalique; Muhammad Dawood; Imran Zahoor (Tropical Animal Health and Production, 2024)

Vanillic Acid Enhances Mung Bean Resistance and Growth Against Macrophomina phaseolina as a Sustainable Antifungal Approach - Numan Ali; Amna Shoaib; Muhammad Rafiq; Barizah Malik; Muhammad Yousaf (Journal of Crop Health, 2024)

The detrimental effect of rainforest conversion to rubber plantations on soil dissolved organic carbon and C: N stoichiometry, mediated by altered soil biogeochemistry - Ashutosh Kumar Singh; Wenjie Liu; Xiai Zhu; Chunfeng Chen; Muhammad Numan Khan; Bin Yang; Xiao Jin Jiang (Journal of Environmental Management, 2024)

Effect of the combination of polyvinyl chloride (PVC) and steel slag waste on the durability and mechanical properties of composite mortars - Md. Alhaz Uddin; Numan Wali; Muhammad Tariq Bashir; Muhammad Ali Sikandar; Fahad Alsharari; Fayez Alanazi; Md. Munir Hayet Khan; Talal O. Alshammari (Innovative Infrastructure Solutions, 2024)

A comprehensive review on the enantiomeric separation of chiral drugs using metal-organic frameworks - Anees Abbas; Muhammad Sheraz Ahmad; Yu-Hsiang Cheng; S. AlFaify; Soohoon Choi; Rana Muhammad Irfan; Arshid Numan; Mohammad Khalid (Chemosphere, 2024)

Soil organic carbon regulation by pH in acidic red soil subjected to long-term liming and straw incorporation - Zhe Shen; Tianfu Han; Jing Huang; Jiwen Li; Nano Alemu Daba; Ntagisanimana Gilbert; Muhammad Numan Khan; Asad Shah; Huimin Zhang (Journal of Environmental Management, 2024)

A unified framework of response surface methodology and coalescing of Firefly with random forest algorithm for enhancing nano-phytoremediation efficiency of chromium via in vitro regenerated aquatic macrophyte coontail (Ceratophyllum demersum L.) - Seyid Amjad Ali; Numan Emre Gümüş; Muhammad Aasim (Environmental Science and Pollution Research, 2024)
Nano-phytoremediation is a novel green technique to remove toxic pollutants from the environment. In vitro regenerated Ceratophyllum demersum (L.) plants were exposed to different concentrations of chromium (Cr) and exposure times in the presence of titania nanoparticles (TiO 2 NPs). Response surface methodology was used for multiple statistical analyses like regression analysis and optimizing plots. The supplementation of NPs significantly impacted Cr in water and Cr removal (%), whereas NP × exposure time (T) statistically regulated all output parameters. The Firefly metaheuristic algorithm and the random forest (Firefly-RF) machine learning algorithms were coalesced to optimize hyperparameters, aiming to achieve the highest level of accuracy in predicted models. The R 2 scores were recorded as 0.956 for Cr in water, 0.987 for Cr in the plant, 0.992 for bioconcentration factor (BCF), and 0.957 for Cr removal through the Firefly-RF model. The findings illustrated superior prediction performance from the random forest models when compared to the response surface methodology. The conclusion is drawn that metal-based nanoparticles (NPs) can effectively be utilized for nano-phytoremediation of heavy metals. This study has uncovered a promising outlook for the utilization of nanoparticles in nano-phytoremediation. This study is expected to pave the way for future research on the topic, facilitating further exploration of various nanoparticles and a thorough evaluation of their potential in aquatic ecosystems. Graphical Abstract

Optimizing potassium and nitrogen fertilizer strategies to mitigate greenhouse gas emissions in global agroecosystems - Jiwen Li; Tianfu Han; Kailou Liu; Zhe Shen; Nano Alemu Daba; Kiya Adare Tadesse; Muhammad Numan Khan; Asad Shah; Zhufeng Wang; Huimin Zhang (Science of The Total Environment, 2024)

Temporal and spatial characteristics of paddy soil potassium in China and its response to organic amendments: A systematic analysis - Tianfu Han; Kailou Liu; Jing Huang; Muhammad Numan Khan; Zhe Shen; Jiwen Li; Huimin Zhang (Soil and Tillage Research, 2024)

Effects of long-term organic and inorganic fertilization on greenhouse gas emissions and soil nutrient stoichiometry in a rice–rice–fallow cropping system - Md Ashraful Alam; Jing Huang; Muhammad Numan Khan; Nano Alemu Daba; Lu Zhang; Zhe Shen; Jiwen Li; Lisheng Liu; Tianfu Han; Nafiu Garba Hayatu; Md Arifur Rahaman; Huimin Zhang (Agriculture, Ecosystems & Environment, 2023)

The role of green finance in mitigating environmental degradation: Empirical evidence and policy implications from complex economies - Umar Numan; Benjiang Ma; Muhammad Sadiq; Hayat Dino Bedru; Can Jiang (Journal of Cleaner Production, 2023)

Impact of long-term fertilization on phosphorus fractions and manganese oxide with their interactions in paddy soil aggregates - Christian Kofi Anthonio; Huang Jing; Chen Jin; Muhammad Numan Khan; Du Jiangxue; Hayatu Nafiu Garba; Li Dongchu; Liu Guangrong; Liu Shujun; Liu Lisheng; Zhang Huimin (Journal of Environmental Management, 2023)

Long-Term Effect of Fertilizations on Yield Sustainability, Soil Organic Carbon Sequestration and Apparent Phosphorus Balance in Acidic Paddy Soil - Hayatu Nafiu Garba; Liu Yiren; Zhang Shuxiang; Liu Kailou; Huang Jing; Lv Zhenzhen; Hou Hongqian; Lan Xianjin; Ji Jianhua; Han Tianfu; Muhammad Numan Khan; Nano Alemu Daba; et al. (Journal of Soil Science and Plant Nutrition, 2022)

Genome-wide identification and characterization of a plant-specific Dof transcription factor gene family in olive (Olea europaea) and its comparison with Arabidopsis - Mariyam; Muhammad Shafiq; Muhammad Haseeb; Rana Muhammad Atif; Syed Agha Armaghan Asad Abbas Naqvi; Numan Ali; Muhammad Arshad Javed; Fizza Gillani; Muhammad Saleem Haider (Horticulture, Environment, and Biotechnology, 2021)

LC–MS/MS-based profiling of bioactive metabolites of endophytic bacteria from Cannabis sativa and their anti-Phytophthora activity - Irum Iqrar; Muhammad Numan; Tariq Khan; Zabta Khan Shinwari; Gul Shad Ali (Antonie van Leeuwenhoek, 2021)

Environmental quality, climate indicators, and COVID-19 pandemic: insights from top 10 most affected states of the USA - Bilal; Muhammad Farhan Bashir; Khurram Shahzad; Bushra Komal; Muhammad Adnan Bashir; Madiha Bashir; Duojiao Tan; Tehreem Fatima; Umar Numan (Environmental Science and Pollution Research, 2021)

Effect of Seawater Ageing on Fracture Toughness of Stitched Glass Fiber/Epoxy Laminates for Marine Applications - Atizaz Hassan; Rafiullah Khan; Numan Khan; Muhammad Aamir; Danil Yurievich Pimenov; Khaled Giasin (Journal of Marine Science and Engineering, 2021)
Composite materials are used in various industries such as marine, aircraft, automotive, etc. In marine applications, composites are exposed to seawater, which can affect their mechanical properties due to moisture absorption. This work focuses on the durability of composite materials under the short-term effect of seawater ageing. The specimens were prepared from glass fiber/epoxy using a hand lap-up method and stitched in the z-direction with Kevlar fiber. The specimens were submerged in seawater for 24 and 35 days. A significant decrease in maximum load was found as specimen immersion time in seawater increased. The seawater ageing also affected fracture toughness with a reduction of 30% for 24 days immersion and 55% for 35 days. The ageing also caused the swelling of composites due to moisture absorption, which increased the weight of the specimens. Compared to the dry specimens, the weight of the specimen for 24 days increases to 5.2% and 7.89% for 35 days’ seawater ageing. The analysis also showed that due to seawater ageing, the de-bonding rate increased as the number of days increased.

Exploring the role of fossil fuels, hydroelectricity consumption, and financial sector in ensuring sustainable economic development in the emerging economy - Faisal Faisal; Muhammad Numan Khan; Ruqiya Pervaiz; Peshraw Majid Muhamad; Mohammad Othman Jamil Rashdan (Environmental Science and Pollution Research, 2021)

Depth Distribution of Bulk and Aggregate-Associated Manganese Oxides Mediated by Soil Chemical Properties in a Long-Term Fertilized Paddy Soil - Christian Kofi Anthonio; Huang Jing; Han Tianfu; Muhammad Qaswar; Liu Kailou; Du Jiangxue; Muhammad Numan Khan; Muhammad Abbas; Sehrish Ali; Lehlogonolo Abner Matelele; Liu Shujun; Liu Guangrong; et al. (Journal of Soil Science and Plant Nutrition, 2020)

Environmental pollution and COVID-19 outbreak: insights from Germany - Bilal; Muhammad Farhan Bashir; Maroua Benghoul; Umar Numan; Awais Shakoor; Bushra Komal; Muhammad Adnan Bashir; Madiha Bashir; Duojiao Tan (Air Quality, Atmosphere & Health, 2020)

Characterization of antifungal metabolites produced by Lactobacillus plantarum and Lactobacillus coryniformis isolated from rice rinsed water - Shazia Anwer Bukhari; Mahwish Salman; Muhammad Numan; Muhammad Rizwan Javed; Muhammad Zubair; Ghulam Mustafa (Molecular Biology Reports, 2020)

Tillage practices improve rice yield and soil phosphorus fractions in two typical paddy soils - Waqas Ahmed; Muhammad Qaswar; Huang Jing; Dong Wenjun; Sun Geng; Liu Kailou; Meng Ying; Tang Ao; Sun Mei; Li Chao; Xu Yongmei; Sehrish Ali; et al. (Journal of Soils and Sediments, 2020)

Pigments from Soil Bacteria and Their Therapeutic Properties: A Mini Review - Roqayya Mumtaz; Samina Bashir; Muhammad Numan; Zabta Khan Shinwari; Muhammad Ali (Current Microbiology, 2019)